Development of an improved steamer for optimum retention of carotenoids in Attieke produced from biofortified cassava (Manihot esculenta Crantz) roots - Alamu, E.O.; Sangodoyin, O.M.; Diallo, T.A.; Kolawole, P.; Olajide, J.O.; Jekayinfa, S.O.; Abass, A.; Tran, T.; Awoyale, W.; Parkes, Elizabeth Y.; Maziya-Dixon, B. (Hindawi Limited, 2023)
Attiéké, made from biofortified (yellow) cassava genotypes, requires a new cooking method to minimize carotenoid degradation during processing. Thus, this research is aimed at designing and building a more efficient steamer to produce high-quality attiéké from biofortified cassava roots. Using three improved biofortified cassava genotypes (IBA141092, IBA070593, and IBA011368) obtained from IITA research farms, attiéké samples were produced using traditional and developed steamers. The results show that the developed steamer outperformed the traditional steamer; it was 1.5 times faster, used less fuel (2.6 times less), and had higher true carotenoid retention. The developed steamer genotype IBA070593 had the highest true retention of 90.4 percent, while the traditional steamer genotype IBA0141092 had the lowest carotenoid retention of 61.9 percent and the highest in the developed steamer (62.4 percent). When compared to the traditional steamer, the developed steamer had better cooking performance and a more extraordinary ability to retain carotenoids. Thus, the developed steamer is recommended for attiéké processors due to its improved cooking performance, and using this steamer to produce attiéké from biofortified cassava will help to alleviate vitamin A deficiency among attiéké consumers.